Plan de promoción y publicidad para el comercial “Lorenita” del cantón Buena Fe - año 2011 - Cedeño Vivas, Lorena Rocío (2011)
Printing in Ecuador has been evolving over time and is a work that has had a significant value in the growth of towns because at the time was used to create basic impressions after giving way to one of the major means communication. Currently in the city of Quevedo printers where there are several different kinds of work done, so it should be emphasized that a marketing plan will help guide it into print in planning with emphasis on the use of methods and strategies to achieve greater recognition consumers of these services and getting more sales and increasing your income. The size of a market depends on the number of people who share the same need to have the resources necessary to offer in return and are willing to provide these resources to get what they want. It was concluded that 79% of the population of printing work done Quevedo, great store and a growing market. Moreover, considering that there are several printers in the city of Quevedo, there is a recognition by consumers mainly in the Printers The Artisan followed by United Printing and Printing Carrillo, the rest are in a smaller range of positioning. For owners of the Independent Press recommended design advertising and promotional strategies to achieve greater opportunities for business growth in the consumer market of the city of Quevedo. It was also recommended to work in home delivery because it is one of the greatest demand services that respondents had in the market Quevedo, also was recommended for the promotion of a trip for its customers.